Can echocardiographic parameters predict mortality in COVID-19?. (14th October 2021) - Babu, A; Eden, N; Meng, Z; Lamb, D; Bhatia, R; Voon, V
Abstract: Introduction: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), otherwise known as the coronavirus (COVID-19) pandemic presents one of the greatest medical challenges of our generation. Whilst commonly causing a viral pneumonitis, myocardial damage has also been suggested by elevated serum troponin values greater than the 99th centile in up to 30% of individuals who require hospitalisation and correlates with increased mortality. Purpose: We aim to identify whether transthoracic echocardiography (TTE) parameters can elucidate the phenomenon of abnormal troponin levels. Furthermore, we seek to characterise the most frequent demographic, biochemical, echocardiographic features and co-morbidities associated with adverse outcomes in this cohort. Methods: A retrospective analysis was conducted utilising electronic patient records of consecutive hospitalised patients with a positive COVID-19 swab between 1st March and 31st October 2020 who underwent a TTE at our institution. Pertinent variables were collected including: the clinical indication, demographics including cardiovascular (CV) risk factors, peak troponin values and fundamental echocardiographic parameters. Results: During this 8-month period, a total of 90 patients underwent a TTE. The mean age of the cohort was 63 years of age and 56% were male. More than half (56.6%) were admitted to the intensive care unit (ICU). A salient 41.1% (n=37) of our cohort succumbed to this devastating virus. Notably, 38.9% (n=35) were of black and minority ethnic origin (BAME). A striking 64.9% (n=24) of patients who died had hypertension. The mean troponin levels were 168.7 ng/L and 176.6 ng/L (0–34 ng/L) in the survivors and non-survivors group respectively. With regards to TTE, the left ventricular parameters were similar between both groups with a mean left ventricular ejection fraction (LVEF) of 60.6% in the non-survivors. Conversely, both right ventricular (RV) dysfunction (37.8%) and raised pulmonary artery systolic pressures (PASP) (51.4%) were markedly more frequent in the patients who perished due to COVID-19 infection. Conclusion: Remarkably, in this extremely ill group of patients who died, 91.9% of patients had a preserved LVEF. There were no overt differences between troponin levels in the survivors and non-survivors. However, hypertension, RV dysfunction and raised PASP were distinctly more prominent in the non-survivors. Thus, providing insight that a normally functioning left ventricle does not preclude to poor outcomes. Overall, this single-centre retrospective study demonstrates that the echocardiographic phenotype associated with mortality is consistent with a severe respiratory illness rather than direct myocardial injury from COVID-19. A multi-modality imaging approach may facilitate the identification of adverse tissue characterisation changes associated with this novel virus as well as guiding further risk stratification and patient management on a case-by-case basis. Funding Acknowledgement: Type of funding sources: None.